Use of Chemometric Tools to Determine the Source of Metals in Sediments of the Rivers of the Turvo/Grande Hydrographical Basin, Sao Paulo State, Brazil - Campanha, Mariele B. [UNESP]; Romera, Joao Paulo [UNESP]; Coelho, Jessica [UNESP]; Pereira-Filho, Edenir R.; Moreira, Altair B. [UNESP]; Bisinoti, Marcia C. [UNESP] (Soc Brasileira Quimica, 2014)
In this work, nine metals were determined in superficial samples and sediment cores obtained from five sampling sites in the Preto, Turvo, and Grande Rivers during the wet and dry seasons. The metals were determined by flame atomization atomic absorption spectrometry. Principal component analysis of the data was performed to evaluate the factors responsible for the variations in metal concentrations. Granulometry and organic matter were the determining factors of metals concentrations. In the Preto River (urban area), high Zn concentrations are due to anthropic sources, whereas the high levels of total nitrogen, Al, Cr, Cu, Fe, K, Mn, and Ni in the Turvo river (damming, rural area) are due to agricultural runoff. Although lower concentrations of metals were observed at the remaining sites, violations of the guide values for sediment quality, particularly for Cr and Mn, indicate the need for management strategies for the Turvo/Grande Hydrographic Basin.
Keywords: Sediments; Metals; Turvo/Grande Hydrographic Basin; PCA; FAAS